KINETIKA REAKSI HIDROLISA KULIT DURIAN MENJADI GLUKOSA DENGAN KALISATOR HCl PADA TANGKI BERPENGADUK - Rachmawati, Emmi; Dewi, Chitra Puspita (UPN VETERAN JAWA TIMUR, 2011)
This study aims to develop mechanisms of the reaction kinetics of hydrolysis into glucose durian skin with HCl catalyst in the stirred tank, to obtain data that is the price reaction kinetics reaction rate constants (k) and activatin energy. The study was condcted after the first with dry skin so that the water content lost durian , durian skin after it is made of powder and sieved to pass 20 mesh particle size, and durian leather was put into a three neck flask with 100 cc of didtilled water was added, as catalyst was added HCl 1N 200 cc and the hydrolysis process carried out in accordance with the time and temperatuure have been determined with a stirring speed of 200 rpm. After the hydrolysis the solution was neutralized by adding NaOH and filtered to take filtrate. Filtrate evaporated, so that is left is then carried out an analysis of concentrated glucose levels using Luff Schrool. Variables run time of hydrolysis 40;50;60;70;80 minutes and the temperature of hydrolysis 75;80;85;90; 95°C. From the results of this study found the greatest conversion is 0.072 at 95°C and time 80 minutes, k obtained by 5,147.10-6e-1038,4710/RT . In this study the following shrinnking core model with chemical reaction as controller, and the reaction followed first order reaction.Key words: Glucose, speed of reaction, activation energy